Segurança no trabalho: especificação de um modelo de inferência fuzzy para avaliação do agente calor - VIEIRA, Alex Sander Záu (Universidade Federal do Pará, 2022)
This article presents a study that consists of a fuzzy inference model specification for the evaluation of heat agents. The structure of model fuzzy used were inputs measured temperature and metabolic rate, while the output was work environment condition that could be salubrious or insalubrious. Through, the inference rules established and according to Brazil legislation about heat, Occupational Hygiene Standard 06, the proposed model can determine the worker conditions about the heat. The validation process is done in three industries from the Industrial Pole of Manaus, therefor all the process necessary for preparations to use the proposed model was described to obtain all the variables necessary in the field. As a result, the proposed model got the correct classification of work environment conditions with pertinent results according to current legislation and technical expertise.